AB0754 Icg-enhanced fluorescence optical imaging detects typical inflammatory changes in asymptomatic subjects with elevated rheumatoid factor or anti-ccp antibodies. (23rd January 2014) - Werner, S. G.; Spiecker, F.; Wiemann, O.; Mettler, S.; Burmester, G. R.; Backhaus, M.; Langer, H.-E.
Abstract : Background: In patients with rheumatoid arthritis (RA) anti-CCP antibodies have been found many years before clinical presentation of active disease (1, 2 ). Elevated rheumatoid factor (RF) in healthy subjects increases the long term risk of RA up to 26-fold and the 10 year absolute risk of RA up to 32% (3 ). ICG enhanced fluorescence optical imaging (FOI) is a new technology offering sensitive imaging detection of inflammatory changes in subjects with arthritis (4 ). Objectives: To report for the first time of typical inflammatory FOI findings in asymptomatic subjects with elevated RA-typical autoantibodies. Methods: Three asymptomatic male individuals (53, 66 and 76 years of age) with elevated IgM-RF (turbidimetric method) (28 IU/ml, 77 IU/ml (ELISA 422 U/ml), 174 IU/ml) and / or anti-CCP antibodies (ratio 0.36, 0.48, 3.79; normal < 1.0) in general practice have been referred to the early arthritis clinic for differential diagnosis. None of the subjects had a history of actual or previous inflammatory joint disease, notably no tender or swollen joints or morning stiffness. Clinical examination was unremarkable; particularly no signs of inflammation were present. CRP was normal (0.1 mg/dl, 0.1 mg/dl, 0.0 mg/dl), ESR was elevated in one subject (8 mm/h, 30 mm/h, 5 mm/h). After informed consent FOI was performed following the usual procedure (4). Results: FOI displayed distinct inflammatory changes in the small joints of the hands (wrist, MCP, PIP) in all subjects. The pathological signal intensities were comparable to findings in active rheumatoid arthritis but showed a marked difference compared to FOI in healthy subjects or in RA patients in clinical remission. Follow-up examinations after 3 months demonstrated an increasing FOI activity in one untreated subject while pathological FOI findings, ESR and RF titer decreased in a second patient with hydroxychloroquine therapy (ESR: 30 -> 14 mm/h; RF: 422 -> 341 U/ml), after 3 and 9 months. Conclusions: These findings may indicate that a stage of subclinical inflammation precedes the clinical onset of active arthritis in the development of RA. With the visualization of typical inflammatory changes in asymptomatic subjects with elevated RF or positive anti-CCP antibodies FOI possibly opens new diagnostic opportunities in preclinical RA. Further investigations with follow up examinations to proof this concept are necessary. References: Rantapää-Dahlqvist S, de Jong BA, Berglin E, et al.: Antibodies against cyclic citrullinated peptide and IgA rheumatoid factor predict the development of rheumatoid arthritis. Arthritis Rheum. 2003 Oct;48(10):2741-9. Nielen MM, van Schaardenburg D, Reesink HW, et al: Specific autoantibodies precede the symptoms of rheumatoid arthritis: a study of serial measurements in blood donors. Arthritis Rheum. 2004 Feb;50(2):380-6. Nielsen SF, Bojesen SE, Schnohr P, Nordestgaard BG.: Elevated rheumatoid factor and long term risk of rheumatoid arthritis: a prospective cohort study. BMJ. 2012 Sep 6;345:e5244. Werner SG, Langer HE*, Ohrndorf S*, et al.*equal contribution: Inflammation assessment in patients with arthritis using a novel in vivo fluorescence optical imaging technology. Ann Rheum Dis. 2012 Apr;71(4):504-10 Disclosure of Interest: None Declared